2023
DOI: 10.1021/acsami.3c07098
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Investigation and Quantitative Analysis of Lithium Plating under Subzero Operation of Lithium-Ion Batteries

Abstract: Safety hazards arising from lithium (Li) plating during the operation of lithium-ion batteries (LIBs) are a constant concern. Herein, this work explores the coaction of low temperatures and current rates (C rates) on Li plating in LIBs by electrochemical tests, material characterization, and numerical analysis. With a decrease in temperature and an increase in C rate, the battery charging process shifts from normal intercalation to Li plating and even ultimately fails at −20 °C and 0.5C. The morphology observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Accordingly, the use of the lithium plating Coulomb efficiency has been proposed to evaluate its reversibility. 33 Yue et al found that the anode could achieve stable cycling when the lithium plating amount reached 40% of the capacity. A 1.2 A h pouch battery was used, which could be cycled for more than 150 times at an ambient temperature of 6 °C with a capacity retention rate of 84.4%, verifying the high reversibility of lithium plating.…”
Section: Lithium-ion Power Single-cell Battery Charging Strategymentioning
confidence: 99%
“…Accordingly, the use of the lithium plating Coulomb efficiency has been proposed to evaluate its reversibility. 33 Yue et al found that the anode could achieve stable cycling when the lithium plating amount reached 40% of the capacity. A 1.2 A h pouch battery was used, which could be cycled for more than 150 times at an ambient temperature of 6 °C with a capacity retention rate of 84.4%, verifying the high reversibility of lithium plating.…”
Section: Lithium-ion Power Single-cell Battery Charging Strategymentioning
confidence: 99%